Peran Orang Tua Dan Guru dalam Meningkatkan Perkembangan Belajar Siswa Kelas II di SDN 2 Batu Nampar - Muhamad Zaril Gapari (Al-Faiza : Journal of Islamic Education Studies, 2024)
Education is one activity that is universal in the life of humans, anywhere There is society, there is also education. Many countries recognize that problem education Is a complicated issue, however, everything feels that education is the State's very duty petting, a nation that wants to progress, build, and try to improve circumstances in society and the world, of course, the state that education is key, and without key business, they will fail. This study aims to determine what role parents and teachers play in improving the learning development of second-grade students at SDN 2 Batu Nampar. This type of research is descriptive qualitative which aims to explain or describe a situation, event, or object such as a person, or anything related to research. Analysis of the data obtained based on data in the field, the analysis process has four stages, namely reduction, triangulation, data presentation, and verification/conclusion. Based on research conducted through interviews, observation, and documentation. The results of this study are (1) The role of parents in enhancing student learning development includes: (a) Parents as motivators, there are 87% of parents performing their role as motivators such as giving gifts, advising to be diligent in worship and study. (b) Parents as facilitators, there are 72% of parents perform their role as facilitators, for example, in places of study, stationery, books, and others. (c) Parents as supervisors, 57% of parents have carried out their role as supervisors such as supervision in a bad environment, promiscuity, and excessive use of gadgets. (2) The teacher's war in improving student learning development includes: (a) The teacher is a model and role model, the teacher gives examples to students, for example, teachers dress neatly, speak well, and apply ethics in learning. (b) As an advisor, the teacher often advises the form of lectures such as reminding them to be diligent in worship and continue studying and giving advice to children who have problems in their families. (c) The teacher is an innovator, the teacher always creates innovations in learning, for example, inviting students to study outside the classroom, inviting students to sing, and using storytelling methods in learning.